Anomalous superficial peroneal nerve with higher division: a case report - Babu, Billakanti Prakash; Thomas, Huban; Mittal, Sachendra; Jee, Kanhiya (International Journal of Research in Medical Sciences, 2017)
The superficial peroneal nerve is one of the terminal branch of common peroneal nerve. There are reports in the available literature about the variant course and distribution of this nerve. The variations of the above nerve are important and provide important information to surgeons during dissection of lower limb. In the present case a rare higher division of superficial peroneal nerve into medial and lateral branches in the leg was seen in an adult male cadaver in left lower limb. Awareness of anatomical variations of superficial peroneal nerve presented here becomes important to avoid injury in clinical situations like pain over the lateral malleolus.